2020
DOI: 10.3390/ijms21114062
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein A-I Supports MSCs Survival under Stress Conditions

Abstract: Clinical trials have shown the safety of mesenchymal stem/stromal cells (MSCs) transplantation, but the effectiveness of these treatments is limited. Since, transplanted MSCs will undergo metabolic disturbances in the bloodstream, we investigated the influence of blood plasmas of type 2 diabetes (T2D) patients on MSCs viability and examined whether apolipoprotein A-I (apoA-I) could protect cells from stressful conditions of serum deprivation (SD), hypoxia, and elevated concentrations of reactive oxygen species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…Apo-AI clearly induces apoptosis by lowering angiogenin production in order to reduce anti-stress function. This indicates that apo-AI not only controls cholesterol homeostasis in the brain, but also has a role in protecting the brain from injury and stress [ 39 ]. The current study contrastingly showed positive correlations between the level of ANG and apo-AI at the baseline, probably reflecting the absence of pathological conditions in the enrolled patients.…”
Section: Discussionmentioning
confidence: 99%
“…Apo-AI clearly induces apoptosis by lowering angiogenin production in order to reduce anti-stress function. This indicates that apo-AI not only controls cholesterol homeostasis in the brain, but also has a role in protecting the brain from injury and stress [ 39 ]. The current study contrastingly showed positive correlations between the level of ANG and apo-AI at the baseline, probably reflecting the absence of pathological conditions in the enrolled patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its role in cholesterol trafficking, Apo-A, a multifunctional protein, participates in inflammatory and immune responses [27]. It also stimulates the proliferation of monocytes, granulocytes and their progenitor cells and bone marrow MSCs [28] and supports MSC survival under stress conditions [29], which might be beneficial for hematopoiesis recovery [20]. Some studies revealed that exogenousfree Apo-A alters the characteristics of progenitor cell populations [30].…”
Section: Discussionmentioning
confidence: 99%
“…In that way, further studies with MSC administration associated with glycemic control in the BTBR ob/ob mice will significantly improve the metabolic and renal therapeutic effects, halting DKD progression and more precisely simulating clinical translational application. Furthermore, it will be a great opportunity to investigate MSCs’ reparative mechanisms in a glucose-controlled setting, which can protect administered cells and enhance their therapeutic effectiveness [ 64 ].…”
Section: Discussionmentioning
confidence: 99%